The enigmatic helicase DHX9 as a candidate prognostic biomarker for resected pancreatic ductal adenocarcinoma - Chen, Le-gao; Cui, Ying; Lu, Wei-qin; Wu, Hao; Jiang, Jin-song; Ding, Ke-feng (Frontiers in Oncology, 2022)
Background Pancreatic ductal adenocarcinoma (PDAC) remains as one of the most lethal malignances and shows limited efficacy to current therapies. The DEAH-box helicase 9 (DHX9) is widely reported to influence cell biological behavior via regulating DNA replication, genomic stability, transcription, translation, and microRNA biogenesis. However, the prognostic role of DHX9 in PDAC remains unclear. Thus, the objective of this study is to investigate the prognostic value of DHX9 expression in PDAC patients. Methods Tumor specimens from PDAC patients undergoing surgical resection were obtained, and DHX9 was stained and analyzed in this study. Univariate and multivariate Cox regression analyses were utilized to identify independent risk factors for overall survival (OS) and recurrence-free survival (RFS). The prognostic nomograms for OS and RFS were established to obtain superior predictive power. Results Among the enrolled 110 patients, 61 patients were identified as high expression of DHX9. The correlation analysis revealed that the higher DHX9 expression in PDAC was prone to have advanced N stage (P=0.010) and TNM stage (P=0.017). For survival, the median OS (21.0 vs. 42.0 months, P<0.001) and RFS (12.0 vs. 24.0 months, P<0.001) of patients in the high DHX9 group was significantly shorter than that in the low DHX9 group. Within the univariate and multivariate analysis, AJCC N stage (P=0.036) and DHX9 expression (P=0.041) were confirmed as independent prognostic factors for OS, while nerve invasion (P=0.031) and DHX9 expression (P=0.005) were for RFS. Finally, the novel prognostic nomograms for OS and RFS were established and showed superior predictive accuracy. Conclusion This study identified the independent prognostic value of DHX9 for RFS and OS in resected PDAC patients, and higher DHX9 expression was prone to have earlier recurrence and shorter OS. Therefore, DHX9 may be a promising and valuable biomarker and potential target for treating PDAC. More accurate and promising predictive models would be achieved when DHX9 is incorporated into nomograms.